Medial pivot designs result in improved patient reported outcome measures and range of motion when compared to cruciate retaining total knee replacements: A systematic review and meta-analysis - Darren Puttock; Akhilesh Pradhan; Pip Divall; Amit Bishnoi; Arijit Ghosh; Seth O'Neill; Randeep Singh Aujla (PLoS ONE, 2026)
Background Knee arthroplasty remains one of the most important treatment options in improving quality of life for patients with end-stage knee osteoarthritis. However, roughly 20% of patients remain dissatisfied with their outcome. Perceived implant instability and range of motion are factors that may contribute to dissatisfaction. The medial pivot (MP) total knee replacement (TKR) is postulated to provide increased stability due to greater implant conformity and replication of anatomical function compared to cruciate retaining (CR) implants. This systematic review and meta-analysis evaluates the impact of MP TKR on patient reported outcome measures (PROMs,) range of motion (ROM), pain scores and functional assessment measures in comparison to traditional CR implants. Methods and findings An extensive literature search of multiple databases was conducted to identify eligible high quality studies which compared PROMs data for MP and CR TKR, with a minimum of 12 months follow-up. Our primary outcome was the forgotten joint score (FJS-12). Secondary outcomes included additions PROMs, ROM data and functional assessments. Risk of bias and quality of research were assessed by GRADE rating and the AMQPP tool respectively. A total of 7 articles were included in the systematic review, encompassing 675 patients aged 59–86 years. Four studies assessed FJS-12, with mean difference of 7.46 (−2.44–17.37) in favour of MP TKRs, which was not statistically significant. Overall, 1415 PROM scores from 675 patients were included, giving a statistically significant difference 0.34 (0.16–0.52) and an effect size of 3.69 (p = 0.0002) in favour of MP designs utilising a standardised mean difference analysis. ROM data demonstrated an overall statistically significant mean difference of 4.63° (1.00–8.27) in favour of MP knees. Further functional outcomes, laxity, power measures demonstrated favourable outcomes for MP knees but were ineligible for inclusion in pooled analyses. Conclusion No statistical difference was observed for the majority of PROMs. PROMs including FJS-12, range of motion and functional outcome scores trended towards favouring MP TKRs; with a statistically significance advantage seen for pooled PROMs scores and ROM. However, there remains limited data relating to functional outcome measures within the literature. Further high-powered, multicentre studies are required to analyse whether MP TKRs are superior to CR TKRs regarding functional outcomes.